STRATEGI BERUSAHA PEDAGANG PAKAIAN BEKAS DI JALAN VETERAN BERASTAGI KABUPATEN KARO - Sinuhaj, Trisna Br; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the profile of used clothing traders on Jalan Veteran Berastagi and to find out the strategy of trying used clothing traders on Jalan Veteran Berastagi. The method used in this study is a qualitative research method, with data collection techniques carried out through observation, interviews and documentation. The subjects in this study were used clothing traders at Jalan Veteran Berastagi, Karo Regency. Determination of informants is done by using purposive sampling technique, as many as 5 informants selected based on certain criteria. Selling used clothes has several strategies that must be carried out by traders, such as promotions, choosing a strategic location, recognizing customers, satisfying consumers, being consistent in trying. These various methods are carried out by traders to maintain their business to increase family income. The strategy in selling is very necessary so that the merchant stays in the running of the business so that it can continue the next generation.  Keywords: Used Clothing Trader, Business Strategy